Development and pathogenicity analysis of full-length infectious cDNA clones of citrus yellow mottle-associated virus in citrus plants - Jia-xing WU; Song ZHANG; Xiao-fei LIANG; Fei XING; Sagheer ATTA; Xue-feng WANG; Meng-ji CAO (Journal of Integrative Agriculture, 2023)
Citrus yellow mottle-associated virus (CiYMaV) belonging to the subgenus Mandarivirus within the genus Potexvirus, was first identified in 2018 from Pakistan (CiYMaV-PK), where it is endemic in several regions. Here, three full-length cDNA clones (pCiYMaV-FL-1, pCiYMaV-FL-18, and pCiYMaV-FL-22) corresponding to the genomic RNA of CiYMaV were constructed and then agroinfiltrated on Chandler pummelo (Citrus grandis) seedlings using the vacuum infiltration method. All the inoculated plants developed severe vein yellowing, leaf mottling, and dwarfing symptoms by 40 days post-infiltration (dpi). The results of a direct tissue blot immunoassay and reverse transcription polymerase chain reaction detection showed 94.7–100% infection rates of pCiYMaV-FL at 60 dpi. Despite there being no observed difference among the three clones in the severity of symptom, pCiYMaV-FL-22 showed the highest accumulation levels of viral RNA and coat proteins. Moreover, pCiYMaV-FL-22 successfully infected seven other citrus varieties and induced symptoms in five of them. Transmission electron microscopy identified the presence of filamentous virus particles in extracts from systemic leaves of the plants infected with pCiYMaV-FL-22 at 6-months post-infiltration. Taken together, the results indicate that Koch's postulates were fulfilled for CiYMaV in citrus plants. This is the first report of full-length infectious cDNA clones of CiYMaV, and thus, the data provide a basis for further study of the molecular mechanisms of virus infection and the development of a viral vector to express foreign genes in citrus plants.